Synthesis of acrylic acid through aldol condensation of acetic acid with formaldehyde catalyzed by Bi‐, W‐ and Cs‐doped B2O3/SiO2 nanocomposites. Issue 7 (29th January 2022) - Wang, Aili; Ye, Chunlin; Yu, Dejian; Ding, Yun; Yin, Hengbo
Abstract: BACKGROUND: Acrylic acid commercially produced by the successively catalytic oxidation of propylene has a high cost. The synthesis of acrylic acid by aldol condensation between coal derivatives, acetic acid and formaldehyde, is an economic alternative to the propylene oxidation process. However, the development of an environmentally friendly and effective catalyst has remained a challenge. RESULTS: Diboron trioxide [B2 O3 (6–20%)]/silica (SiO2 ) nanocomposites with B2 O3 particle sizes of 1–2 nm prepared by the wetness impregnation of boric acid into silica aerogel and subsequent calcination at 500 °C effectively catalyzed the gas‐phase aldol condensation reaction between acetic acid and formaldehyde (trioxymethylene) to acrylic acid with a selectivity of ≈87% at 340–400 °C. Bismuth (Bi‐), tungsten (W‐) and caesium (Cs)‐doped B2 O3 /SiO2 nanocomposites had higher catalytic activities in the gas‐phase aldol condensation reaction to acrylic acid than the undoped B2 O3 /SiO2 nanocomposite. CONCLUSION: Weak‐strength Lewis acid and alkali sites of the B2 O3 (6–20%)/SiO2 nanocomposites co‐catalyzed the aldol condensation reaction to form acrylic acid. The doping of B2 O3 /SiO2 nanocomposites with Bi, W and Cs components results in the formation of BiBO3, WO3 and CsBO2 phases, which lead to an increase in acidity and basicity resulting in higher catalytic activity in the formation of acrylic acid. © 2022 Society of Chemical Industry (SCI).